Economic Function of Corporate Image - Drūteikienė, Greta (Ekonomika, 2003)
Economic, political and social changes taking place in Lithuania are closely linked with globalisation and economic integration of the world. The aspiration of Lithuania to integrate into international organisations mirrors a part of this globalisation and is one of the most important priorities of domestic and foreign policy of the state. Fulfilment of this aspiration will play a decisive role in defining the place of Lithuania as a state in Europe.With Lithuania’s integration into the European Union, ensuring efficiency, continuity and competitiveness on new markets of organisations of our country are one of the most relevant issues of management and economy. Within the said circumstances, a good image becomes a necessary precondition for an organisation aiming at sustainable, long-lasting and successful business. It attracts new clients and partners, promotes sales and raises their volumes, increases possibilities for an organisation to make use of external financial resources, necessary qualitative resources and in this way stimulates dynamic development of an organisation.An image gives an organisation exceptional competitive advantage, since it is unique and cannot be bought and copied. The essential thing is that the image is attributed to intangible assets of an organisation as it helps to create its value-added.